Case report: Early thrombosis in left atrial during transcatheter closure of ASD in a child with favorable outcome after use of GPIIb/IIIa receptor antagonist and heparin - Wang, Hui; Zhu, Zhiwei; Liu, Zhenyu; Yuan, Yonghua; Xu, Xuan; Liu, Liping; Wen, Jie; Xia, Xiaohui; Zhang, Yu; He, Jin (Frontiers in Pediatrics, 2023)
Background Acute thrombus in atrial septal defect occluders is a rare complication that requires aggressive, effective, and safe management. Tirofiban, a platelet glycoprotein IIb/IIIa receptor antagonist, is widely used for the management of thromboembolic diseases, such as coronary heart disease and stroke. To date, there is no report using the GPIIb/IIIa receptor antagonist tirofiban for the management of ASD closure-related thrombosis in children. Case presentation Herein, we reported a case of a 5-year-old girl with ASD who presented with acute thrombus on the left disc of the occluder device immediately after transcatheter closure of ASD. The thrombus was successfully dissolved 24 h after a combined infusion of heparin and tirofiban, followed by 1 months of aspirin and clopidogrel and 5 months of aspirin alone. No thromboembolism or hemorrhage events occurred during follow-up for more than 2 years. Conclusion The continuous infusion of GPIIb/IIIa receptor antagonist tirofiban combined with heparin may have beneficial effects for the management of thrombosis during ASD closure procedure.